The incidence of the use of english cognates and lexical network in the english learning process for english proficeincy students at University of the Armed Forces ESPE in the supporting center 45 Otavalo from september 2011 to february 2012 - Montalvo Dávila, Natalia Samanta (2014)
A variety of studies has demonstrated that bilingual processes form similar cognates different from other words. One finding is that the cognate facilitation effect makes that bilinguals produce and recognize cognates faster than non-cognates. This effect is present in processing of either language of a bilingual person, though it is more pronounced in non-dominant language processing. Cognates can be stored similarly in different morphological forms of a word (especially in the case of regular correspondence patterns): they are somewhat different phonologically, and yet are considered the same word...